2017
DOI: 10.1038/srep43242
|View full text |Cite
|
Sign up to set email alerts
|

ZYZ-168 alleviates cardiac fibrosis after myocardial infarction through inhibition of ERK1/2-dependent ROCK1 activation

Abstract: Selective treatments for myocardial infarction (MI) induced cardiac fibrosis are lacking. In this study, we focus on the therapeutic potential of a synthetic cardio-protective agent named ZYZ-168 towards MI-induced cardiac fibrosis and try to reveal the underlying mechanism. ZYZ-168 was administered to rats with coronary artery ligation over a period of six weeks. Ecocardiography and Masson staining showed that ZYZ-168 substantially improved cardiac function and reduced interstitial fibrosis. The expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…This is particularly interesting, since NFκ B has been shown to induce myofibroblast differentiation and fibrosis in pulmonary and hepatic fibrosis (Luedde and Schwabe 2011; Dong and Ma 2019). SMAD2/3 and ERK1/2 activation by TGFβ are central mechanisms of the fibrotic signaling cascade (Khalil et al 2017;Khalil et al 2017;Luo et al 2017) and modulation of these pathways has been proposed to affect cardiac and non-cardiac fibrosis (Rosenbloom et al 2013;Cheng et al 2016;Khalil et al 2017;Li et al 2018). In a murine model of pressure overload, selective block of SMAD2/3 signaling drastically attenuated fibrosis (Khalil et al 2017).…”
Section: Mesalazine Acts As a Dual Inhibitor Of Smad2/3 And Erk1/2 Phmentioning
confidence: 99%
“…This is particularly interesting, since NFκ B has been shown to induce myofibroblast differentiation and fibrosis in pulmonary and hepatic fibrosis (Luedde and Schwabe 2011; Dong and Ma 2019). SMAD2/3 and ERK1/2 activation by TGFβ are central mechanisms of the fibrotic signaling cascade (Khalil et al 2017;Khalil et al 2017;Luo et al 2017) and modulation of these pathways has been proposed to affect cardiac and non-cardiac fibrosis (Rosenbloom et al 2013;Cheng et al 2016;Khalil et al 2017;Li et al 2018). In a murine model of pressure overload, selective block of SMAD2/3 signaling drastically attenuated fibrosis (Khalil et al 2017).…”
Section: Mesalazine Acts As a Dual Inhibitor Of Smad2/3 And Erk1/2 Phmentioning
confidence: 99%
“…In addition, ROCK2 was shown to contribute to cardiac hypertrophy [8,11]. In vitro, ROCKs regulate fibrosis-associated genes, including connective tissue growth factor (CTGF), fibroblast growth factor 2 (FGF2), α-smooth muscle actin (SMA) and pro-collagen I [10,[13][14][15]. ROCKs are also implicated in cardiac fibroblast migration and proliferation [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In the mouse model of myocardial infarction, Rock1 −/− and Rock1 +/− mice showed reduced cardiac fibrosis [15,16]. Similar protective effects were observed in animals treated with pharmacological ROCK inhibitors fasudil or ZYZ-168 [17][18][19][20]. The profibrotic role of ROCK1 and ROCK2 has been also demonstrated in models of hypertension induced with angiotensin II infusion or by transverse aortic constriction [16,18,[21][22][23].…”
mentioning
confidence: 53%
“…Furthermore, in our model, the stimulation of Rock1 +/− cardiac fibroblasts with TGF-β resulted in reduced Erk phosphorylation. Impaired Erk activation has been also observed in TGF-β-activated cardiac fibroblasts treated with ROCK inhibitor ZYZ-168 [20] and in postinfarcted hearts of rats receiving ROCK inhibitor fasudil [19]. These data suggested that ROCKs could enhance canonical and noncanonical TGF-β downstream molecular responses, and a positive feedback loop mechanism could serve as a potential explanation.…”
Section: Discussionmentioning
confidence: 76%